الكفاءة الإستخدامية للمناطق المكشوفة والخضراء لكلية الزراعة (Journal of Engineering, 2007)
The main goal of planning and designing for external open spaces and gardens is to create a comfortable external environment for human use. In this environment, there should be a balance between the function and the aesthetic, taking into account the location’s circumstances, specialty, characteristic and economic potentials. The research is aimed at limiting the disadvantages and the problems of the opening areas and gardens in the agriculture college supported by study of the similar Arabic countries experience that have the same Iraq circumstances environment.Also building a data base that may be a work sheet to improve, develop and ever-living these opening green areas and maintain and act it in the form that achieves the purpose behind it’s establishment. The study includes a theorem side which includes illustration of foundations of planning , designing and maintain the gardens and the external infected factors and show the Arabic countries experience, and application side that includes limiting the problems and disadvantages of the opening areas and gardens in the agriculture college and the information form as well as the development suggestions